2010
DOI: 10.1111/j.1399-5448.2009.00527.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucose tolerance status in 510 children and adolescents attending an obesity clinic in Central Italy

Abstract: Glucose metabolism alterations are frequently found among children and adolescents with overweight/obesity from Central Italy. Age, fasting glucose, and insulin resistance are main predictors of IGT. We suggest the use of OGTT as a screening tool in obese European adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
39
6
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 35 publications
9
39
6
5
Order By: Relevance
“…17 In our study, prevalence of IGT was 12% which was consistent with 17.1% and 11.2% in different studies done in Bangladesh 17 and abroad. 18 The prevalence of diabetes mellitus was 6%, this figure was also consistent with other studies where it was 4%. 19 In present study, the prevalence of high SGPT among obese children was 36%.…”
Section: Discussionsupporting
confidence: 81%
“…17 In our study, prevalence of IGT was 12% which was consistent with 17.1% and 11.2% in different studies done in Bangladesh 17 and abroad. 18 The prevalence of diabetes mellitus was 6%, this figure was also consistent with other studies where it was 4%. 19 In present study, the prevalence of high SGPT among obese children was 36%.…”
Section: Discussionsupporting
confidence: 81%
“…BMI, IL-6, neopterin, fibrinogen, CRP, and Lp-PLA 2 lar diseases [27,28]. In this study, we demonstrated marked increases of IL-6, neopterin and Lp-PLA 2 in obese adolescents with elevated glucose level at 30 min compared to NGT and IGT groups.…”
Section: Biochemical Analysismentioning
confidence: 47%
“…Obesity is associated with alterations in glucose metabolism that may be present in adolescents. OGTT is a screening tool necessary to assess the risk of alterations in glucose metabolism in obese adolescents [27,28]. In our clinic, all adolescents with obesity, defined as having a BMI equal to or greater than the age-and sexspecific cutpoints, undergo 2-h OGTT.…”
Section: Discussionmentioning
confidence: 99%
“…Namun, apakah obesitas terjadi pada awal atau setelah hiperinsulinemia masih belum diketahui pasti. Secara konseptual, mekanisme yang diusulkan untuk menjelaskan kausalitas adalah mekanisme penumpuk- 16 di sebuah klinik obesitas di Italia, juga ditemukan bahwa obesitas lebih banyak pada anak laki-laki (56,7%) daripada anak perempuan (43,3%). Pada penelitian kami, anak obes yang mengalami resistensi insulin didapatkan 34 (63%) sampel, di antaranya 23 (67,6%) berjenis kelamin laki-laki, dan 11 (32,4%) anak perempuan.…”
Section: Pembahasanunclassified